A small payload desktop industry robot design without conventional reducers - Han, Xiaolei; Liu, Peng; Zhang, Jiaqi (IAES International Journal of Robotics and Automation (IJRA), 2024)
Designing a compact desktop industrial robot with a small payload capacity, eliminating the use of traditional reducers, poses an intriguing challenge. This innovative approach aims to enhance the robot's cost-efficiency and reduce its overall size. The design focuses on optimizing the mechanical structure and exploring alternative mechanisms to achieve precise control without relying on conventional reducers. This article delves into the design aspects of a 1 kg payload robot. Initially, the paper presents an overview of the robot's mechanism and its kinematic analysis. Subsequently, synchronous belts are proposed as replacements for traditional reducers, accompanied by an introduction to the mechanical structure. Simulation is carried out to calculate the drive forces on the belts. According to the result, a suitable belt scheme has been designed. Ultimately, a prototype of the robot is constructed, and experiments demonstrate that this design achieves a repeatable accuracy comparable to robots employing conventional reducers, all while considerably reducing the overall cost of the robot.